1998
DOI: 10.1046/j.1365-2656.1998.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the nitrogen limitation hypothesis in non‐cyclic populations of cotton rats (Sigmodon hispidus)

Abstract: Summary 0[ Nitrogen!containing nutrients have long been considered a frequently limiting resource to the growth of herbivore populations "nitrogen limitation hypothesis#[ To explore this hypothesis\ we examined the relationships between availability of essential amino acids and concentrations of phenolics in the diets of hispid cotton rats "Sigmodon hispidus# in central Oklahoma and the intrinsic characteristics of their non!cyclic populations[ We posited that lower quality proteins "i[e[ essential amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 48 publications
5
40
1
Order By: Relevance
“…We used an estimate of dietary nitrogen from field data collected at CSEAR for S. hispidus (3.16% N, n=52; Clark 2003) that was based on nitrogen analysis of stomach contents (samples collected in April and August 2000) coupled with regressions developed between stomach and dietary nitrogen (Clark et al 2003b). Our estimate was within the range of previously recorded estimates for S. hispidus in central Oklahoma (seasonal range 2.6-4.3% N; Schetter et al 1998). We obtained an estimate of dietary nitrogen from the literature for P. leucopus (4% N; Derting and Hornung 2003) and used this estimate for R. fulvescens, R. montanus, and P. maniculatus because diets of these species primarily comprise insects and seeds (Wilkins 1986;Stancampiano and Caire 1995).…”
Section: Nitrogen Output Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…We used an estimate of dietary nitrogen from field data collected at CSEAR for S. hispidus (3.16% N, n=52; Clark 2003) that was based on nitrogen analysis of stomach contents (samples collected in April and August 2000) coupled with regressions developed between stomach and dietary nitrogen (Clark et al 2003b). Our estimate was within the range of previously recorded estimates for S. hispidus in central Oklahoma (seasonal range 2.6-4.3% N; Schetter et al 1998). We obtained an estimate of dietary nitrogen from the literature for P. leucopus (4% N; Derting and Hornung 2003) and used this estimate for R. fulvescens, R. montanus, and P. maniculatus because diets of these species primarily comprise insects and seeds (Wilkins 1986;Stancampiano and Caire 1995).…”
Section: Nitrogen Output Modelsupporting
confidence: 78%
“…For example, dietary quality is likely to be lower during dormant seasons (e.g., winter), which would cause variation in nitrogen consumption. However, Schetter et al (1998) found that nitrogen content of S. hispidus diets remained high (>2.5% N) throughout the year in central Oklahoma as a result of selective foraging.…”
Section: Discussionmentioning
confidence: 93%
“…For herbivores, forage quality is to a considerable degree determined by nitrogen content, which is often a primary limiting factor for the growth of populations (nitrogen limitation hypothesis [27][28][29][30]). Nitrogen levels in plants vary in response to a range of biotic and abiotic factors, such as weather, leading to both spatial and temporal variation in its availability to herbivores [31][32].…”
Section: Introductionmentioning
confidence: 99%
“…We chose two of the most common species in the southern prairie, the hispid cotton rat (Sigmodon hispidus; Cameron and Spencer 1981) and the fulvous harvest mouse (Reithrodontomys fulvescens; Spencer and Cameron 1982), because of their dominant position by biomass and numbers within the ecosystem (Schetter et al 1998;Brady and Slade 2001;Clark et al 2005) and the difference in their diets. Cotton rats are primarily herbivores, consuming a mixture of monocots and dicots (Randolph et al 1991), whereas the harvest mouse is an omnivore with a substantial insect component (Meserve 1976;Vasquez et al 2004).…”
Section: Introductionmentioning
confidence: 99%